2023
DOI: 10.37934/araset.30.1.132144
|View full text |Cite
|
Sign up to set email alerts
|

Structural Elucidation of the Masp1 and Masp2 Protein from Nephila Pilipes Web Via Bioinformatics Approaches

Abstract: Major ampullate spidroin (MaSps) from orb-weaver spp spider has recently gained interest due to its exceptional characteristics. The biomechanical and biochemical properties from MaSps offer potential in harvesting and exploiting MaSps as a promising bio-based product. However, the current research on the structural elucidation focused more onto the Nephila clavipes spider web rather than the Nephila pilipes which are more common in this region. Herein, this study integrates the used of computational power and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The 3D structure was predicted by the Swiss model ( Fig. 1 b) [ 45 ]. The secondary structure showed that the S protein has 29.59 % α helixes, 4.08 % β sheets, and 44.30 % random coil, extended strand 22.07 % loops ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The 3D structure was predicted by the Swiss model ( Fig. 1 b) [ 45 ]. The secondary structure showed that the S protein has 29.59 % α helixes, 4.08 % β sheets, and 44.30 % random coil, extended strand 22.07 % loops ( Fig.…”
Section: Resultsmentioning
confidence: 99%